2021
DOI: 10.3389/fenvs.2021.760675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forestry on Carbon Emissions in China: Evidence From a Dynamic Spatial Durbin Model

Abstract: Research has proved the significance of forests in controlling carbon emissions, however, our research sheds light on the management of existing forests to combat climate change. To examine the role of forestation and forest investment activities, dynamic spatial techniques are used for 30 provinces of China. The results suggest that forest investment and management not only reduce carbon locally but also in neighboring provinces. Furthermore, the findings of the current study confirmed that forest investment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…In another global study, Lawrence et al (2022) found that the net cooling effect of forests (the net of biophysical and biochemical effects) is substantial, which also includes favorable spatial spillover effects. Similar results are reported by Li et al (2021) for 30 provinces in China. Muhammad et al (2020) analyzed the effects of trade on CO 2 emission and found that these effects are statistically significant, though their signs and magnitudes can vary across income groups.…”
Section: Methodssupporting
confidence: 88%
“…In another global study, Lawrence et al (2022) found that the net cooling effect of forests (the net of biophysical and biochemical effects) is substantial, which also includes favorable spatial spillover effects. Similar results are reported by Li et al (2021) for 30 provinces in China. Muhammad et al (2020) analyzed the effects of trade on CO 2 emission and found that these effects are statistically significant, though their signs and magnitudes can vary across income groups.…”
Section: Methodssupporting
confidence: 88%
“…Resultantly, the public health degrades due to the high emission of greenhouse gasses. It has been proved that an excessive amount of carbon in the atmosphere destabilizes the environment, which adversely affects human health and increases hospitalization and deaths ( 19 22 ). Previously, few studied attempted to examine the nexus, however, as far our limited knowledge, the study is the pioneer which empirically investigated this nexus using GCC data.…”
Section: Introductionmentioning
confidence: 99%
“…The essence of regional ecological environment problems is population and environmental issues, and studying the impact of lifestyles on the environment is important for improving the natural environment (Li et al, 2021b;Sarwar et al, 2021;Mighri et al, 2022;Sarwar, 2022;Sarwar et al, 2022). The change of human living environment has a controversial effect on the ecological environment.…”
Section: Introductionmentioning
confidence: 99%